1, 2, 3, 4‐Tetrahydronaphthalene (vapour) [Air Monitoring Methods, 2014]. Issue 2 (27th April 2016) - Tschickardt, M.; Bremer, S.; Hebisch, R.; Hartwig, A.; ,
Abstract : This analytical method is a validated measurement procedure for the determination of gaseous 1, 2, 3, 4‐tetrahydronaphthalene and for monitoring its MAK value at workplaces. Sampling is performed by drawing a defined volume of air through an adsorption tube filled with Chromosorb 106. The flow rate can be set in the range from 5 to 60 mL/min with a recommended air sample volume of 1.2 L whereas the sampling time must be adjusted to the corresponding flow rate. The collected 1, 2, 3, 4‐tetrahydronaphthalene is thermally desorbed and then analysed by means of gas chromatography fitted with two detectors, a flame ionisation detector (FID) for quantification and a mass selective detector (MSD) for identification and quantification. The quantitative determination is based on a calibration function obtained by means of a multiple‐point calibration using 1, 2, 3, 4‐tetrahydronaphthalene as external standard. The limit of quantification (LOQ) is determined on the basis of aliquots from 1 to 10 mL of the calibration gas in the lower concentration range. The relative LOQ is 0.1 mg/m 3 with a mean recovery of 99%. The expanded uncertainty for this procedure is between 16 and 17%.